A comparative study of instabilities in forced reacting plumes of nonpremixed flames. Issue 3 (August 2016) - Jiang, Jieyu; Jing, Liyue; Zhu, Min; Jiang, Xi
Abstract: A comparative study has been performed to investigate the flow instabilities and their interaction for nonpremixed methane-air flames using experimental results, numerical simulations and theoretical analyses. The effects of buoyancy and the strong external perturbations on the vortex dynamics and instabilities of forced reacting plumes are studied. Results suggest that the flame surface breaks in forced reacting plumes and two flame fronts are formed eventually due to the convective instability coupled with buoyancy-driven instability. Flame pinch-off could occur in a short time for the cases with the strong perturbations of low frequencies. This indicates that the nonpremixed flame system exhibits a low-pass characteristic, which is sensitive to the low frequency perturbations. In addition, the buoyancy instability can be observed from the comparisons, which is of an absolute unstable nature. Despite the fact that theoretical analyses are derived from the single transport equation for mixture fraction with a number of assumptions, the results are still in good agreement with those obtained from the experiments and numerical simulations. Highlights: The flow instabilities of nonpremixed methane-air flames are investigated. The experimental, numerical and theoretical studies show qualitative agreements. The flow convective instability is coupled with buoyancy-driven instability. The nonpremixed flame system exhibits a low-pass characteristic.